Strategic feeding of ammonium and metal ions for enhanced GLA-rich lipid accumulation in Cunninghamella bainieri 2a1 - Shuib S.; Wan Nawi W.N.N.; Taha E.M.; Omar O.; Abdul Kader A.J.; Kalil M.S.; Abdul Hamid A. (Hindawi Publishing Corporation, 2024)
Indexed by WOS/ Scopus